Strategi Pencapaian Kinerja Bidang Bina Pemerintahan Desa pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Probolinggo dengan Pendekatan Analisis SWOT - Arik Agus Setiyowati; Ernani Hadiyati; Gendut Budi Wahyono (Universitas Batanghari Jambi, 2023)
The purpose of this study is to explain the results of the SWOT analysis of the strategy for achieving performance in the Village Government Development Sector at the Community and Village Empowerment Service in Probolinggo Regency. This research use desciptive qualitative approach. The determination of respondents used a saturated sampling technique, namely all employees in the Village Government Sector, totaling 10 people, were used as informants. The data analysis model uses SWOT analysis with the calculation of IFAS and EFAS values. The results of the study show that the strategic plan for achieving the performance of the Village Government Development Sector is in quadrant-3. The strategy that must be implemented is to support turn around, namely taking advantage of external opportunities to improve internal weaknesses.